The Challenges of Covid-19 National Economic Recovery in Indonesia: The Need for Accountability during Emergency - Ayuni, Qurrata (UNIB Press, 2023)
This paper discusses the challenge of accountability of Indonesia national economic recovery policies in the COVID-19 pandemic emergency. There are pros and cons to ensuring the accountability of the national economic recovery policy in the legal and legislative aspects. This paper finds three main issues; First, there is an oversized power that the government has in reallocating the state budget. Second, there is the potential for immunity for irregularities in state finances with the argument of national economic recovery. Third, the need for checks and balances from the state power branch to carry out supervision. Using a normative juridical study, this paper emphasizes the importance of the role of the legislative and judicial branches of power in ensuring accountability for the use of state finances on the pretext of a COVID-19 emergency